2016
DOI: 10.4172/2161-1165.1000e120
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Cardio-Renal Disease: Implications for Minority Populations

Abstract: Obesity is a major public health problem that is reaching pandemic proportion. Currently two thirds of the American population is either overweight or obese and worldwide, 39% of the population is overweight and 13% are considered obese [1,2]. This rapid rise in obesity is associated with increased in diabetes mellitus type 2 (DM2), hypertension (HTN), chronic kidney disease (CKD) and cardiovascular diseases (CVD), the major killer of adults in the USA. Parallel to this epidemic is the rapid rise of sleep diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…OSAS can be related to cardiovascular and metabolic disorders, high blood pressure, diabetes, obesity, coronary artery illness [23,24], stroke, and heart failure [25,26]. OSAS can also cause cellular injury in the central nervous system (CNS) [27].…”
Section: Discussionmentioning
confidence: 99%
“…OSAS can be related to cardiovascular and metabolic disorders, high blood pressure, diabetes, obesity, coronary artery illness [23,24], stroke, and heart failure [25,26]. OSAS can also cause cellular injury in the central nervous system (CNS) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSA, estimated as Apnea Hypopnea Index / Respiratory Disturbance Index (AHI/ RDI) greater than 5, varies between 9% and 38% (men 13-33%, women 6-19%) in the adult population [9]. SD is a common finding in obesity; in fact it has been reported that almost 70% of patients with OSA are obese and most of them develop obesity-related cardiovascular risk factors [10][11][12].…”
Section: Obesity and Sleep Disturbancementioning
confidence: 99%
“…Not only is obesity one of the main causes of OSA, affecting 70% of the patients with OSA, it also shares some of the underlying pathophysiologic mechanisms with obesity-related diseases, such as DM2, HTN and CVD [3,4]. Furthermore, OSA increases risk of end-organ damage in critically ill patients.…”
Section: Introductionmentioning
confidence: 99%